PRICE SETTING IMPLEMENTED BY TRADERS IN THE TRADITIONAL RETAIL STORE IN SARANGAN LAKE TOURIST AREA - Gading, Darisnan Paramu; Mulawarman, Aji Dedi (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to determine the form of price setting applied by traders in traditional retail stores, factors that affect the price setting, and implementation of Javanese culture that embraced community Sarangan the price setting process. Studies using ethnometodology method for analyzing indexicality and reflexivity in the process pricing of goods sold, mark-up decision-making, and determining the selling price. The study found in the price-setting process, the traditional retail traders to apply the principles of Javanese culture among tepa selira, rame ing gawe sepi ing pamrih, nerima ing pandum, and lumintu. The selling price is formed by the merchants of the components of cost of goods sold plus a mark-up or profit which is desired.  Keywords: qualitative, ethnometodology, cost of goods sold, mark up, the selling price